ІНФОРМАЦІЙНО-ПРОГРАМНЕ ЗАБЕЗПЕЧЕННЯ ПОФІДЕРНОГО АНАЛІЗУ Й ОПТИМІЗАЦІЇ ВТРАТ ЕЛЕКТРОЕНЕРГІЇ У РОЗПОДІЛЬНИХ ЕЛЕКТРОМЕРЕЖАХ З РОЗОСЕРЕДЖЕНИМ ГЕНЕРУВАННЯМ - Кулик, В.В.; Бурикін, О.Б.; Глоба, О.В. (Інститут електродинаміки Національної академії наук України, 2017)
The ways of solving the problem of the feeder-balance analysis of electric power losses in distribution electric networks (DEN) using the available information support are considered. Imperfection of the systems of commercial and technical metering of electric power, changes in the transmission patterns of electric power, as well as the effect of distributed electric power sources (DES) make it very difficult to solve the problem. A new approach and software implementation of the feeder analysis of electric power losses is proposed to determine the directions for increasing the energy efficiency of DEN. It consists in parallel calculations and comparison of the results of the feeder-balance electricity and the element-wise determination of losses on the basis of a single information support. References 3, figure, table.